2019
DOI: 10.1186/s12882-019-1237-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying on admission patients likely to develop acute kidney injury in hospital

Abstract: Background The incidence of Acute Kidney Injury (AKI) continues to increase in the UK, with associated mortality rates remaining significant. Approximately one fifth of hospital admissions are associated with AKI and approximately a third of patients with AKI in hospital develop AKI during their time in hospital. A fifth of these cases are considered avoidable. Early risk detection remains key to decreasing AKI in hospitals, where sub-optimal care was noted for half of patients who developed AKI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Therefore, AKI has a significant economic burden as it is estimated to cost the UK National Health Service (NHS) approximately £1.02 billion annually [9]. However, as many as one in five cases of AKI are thought to be preventable [10]. Therefore, with adequate measures to reduce AKI risk, effective monitoring of patients, and with the implementation of appropriate interventions, the NHS could save up to £200 million a year [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, AKI has a significant economic burden as it is estimated to cost the UK National Health Service (NHS) approximately £1.02 billion annually [9]. However, as many as one in five cases of AKI are thought to be preventable [10]. Therefore, with adequate measures to reduce AKI risk, effective monitoring of patients, and with the implementation of appropriate interventions, the NHS could save up to £200 million a year [9].…”
Section: Introductionmentioning
confidence: 99%
“…Renal function is an important component of the SOFA score, but this study did not explore direct associations of clinical signs with AKI . Argyropoulos et al searched for risk factors which could assist in identifying those at risk for AKI upon ICU admission and created models that could quite accurately predict the occurrence of AKI . This study however only used laboratory data (such as urea and albumin) and defined AKI based on creatinine criteria only .…”
Section: Discussionmentioning
confidence: 99%
“…Argyropoulos et al searched for risk factors which could assist in identifying those at risk for AKI upon ICU admission and created models that could quite accurately predict the occurrence of AKI . This study however only used laboratory data (such as urea and albumin) and defined AKI based on creatinine criteria only . Studying patients with septic AKI, Lara et al found that abnormal CRT in 95 septic patients with hyperlactatemia was associated with the need for RRT .…”
Section: Discussionmentioning
confidence: 99%
“…In large, high-dimensional networks of populations with multiple and varying datapoints describing individual features, determining clusters is beyond human action but well within the scope of powerful AI systems. Such AI-based decision systems are already in development in the healthcare context, particularly in the context of Acute Kidney Injury (Argyropoulos et al 2019 ). Google DeepMind’s initially developed a machine capable of playing the ancient Chinese game of Go (DeepMind 2019 ).…”
Section: Methodsmentioning
confidence: 99%